(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
In the contemporary context, the adoption of effective policies against the mafia phenomenon seems particularly complicated and difficult. Indeed, such policies presuppose a precise definition of legitimate power, as an authorized competence on the basis of legal rules defining the limits of form and content of its own exercise. Instead, today, real power seems to come out of the rigidly defined legacy of the legal definition, placing itself elsewhere, within a "space" that allows and facilitates the interaction between subjects, actors, and sodals that are not clearly qualifiable as criminals or as legally operating. All this seems even clearer if read in the light of the neoliberal matrix epochal transformations that have led to the mutation of some fundamental aspects of law and political-institutional articulation, by investing first of all the concept of power and the notion of legality. Keywords: legal powers, criminal powers, neoliberalism, legal transformation, Constitution